Knowledge Level of Farmers on Sugarcane Production Technology in Badaun District of Uttar Pradesh - Rajeev Singh Chauhan1 , Rupendra Kumar , Yagya Dev Mishra , Punit kumar and J.P. Singh (Indian Journal of Extension Education, 2018)
Sugarcane is one of the major crops of Uttar Pradesh. But, sugarcane productivity of Uttar Pradesh remainedvery low as compared to southern states, which may be due to lack of farmers’ knowledge and its practiceabout recommended sugarcane production technologies. Keeping this in view, present study was conducted inAsafpur block of Badaun district in Bareilly division of Uttar Pradesh. A randomly selected sample of 250sugarcane growing farmers was interviewed with the help of an interview schedule. It was found that majorityof large and medium farmers possessed good knowledge regarding soil, seed, fertilizer and irrigationtechnologies of sugarcane crop while it is reverse in case of small farmers.